2013
DOI: 10.1021/ac400761e
|View full text |Cite
|
Sign up to set email alerts
|

Glycomic Analysis Using Glycoprotein Immobilization for Glycan Extraction

Abstract: Glycosylation is one of the most common protein modifications and is involved in many functions of glycoproteins. Investigating aberrant protein glycosylation associated with diseases is useful in improving disease diagnostics. Due to the non-template nature of glycan biosynthesis, the glycans attached to glycoproteins are enormously complex; thus, a method for comprehensive analysis of glycans from biological or clinical samples is needed. Here, we describe a novel method for glycomic analysis using glycoprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
138
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 65 publications
(139 citation statements)
references
References 33 publications
1
138
0
Order By: Relevance
“…Many studies on N-glycans have shown that unmodified sialic acids are fragile and easily lost during sample preparation and ionization in MALDI or even ESI 2024 . Chemical modification of sialic acids, such as amidation 22,25 , methyl esterification 26,27 and perbenzolylation 28 , is commonly used for sialic acid stabilization.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies on N-glycans have shown that unmodified sialic acids are fragile and easily lost during sample preparation and ionization in MALDI or even ESI 2024 . Chemical modification of sialic acids, such as amidation 22,25 , methyl esterification 26,27 and perbenzolylation 28 , is commonly used for sialic acid stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to stabilize sialic acid residues using an in-solution chemical reaction because of the similarities between the chromatographic properties of these chemicals and those of the modified glycans. It is thus difficult to remove these excess chemicals from the modified glycans 20 . Permethylation of the released glycans can protect sialic acids on both N- and O-glycans 29,30 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations